IMAGE OF MOTHER MARY IN CLASSICAL TURKISH LITERATURE - Mustafa, Aycicegi Bunyamin (Літературний процес: методологія, імена, тенденції, 2017)
Image of Mother Mary has a special meaning in Islam. There is even a sura with such title in the Quran that demonstrates the high morality of the woman and her authority. According to the Quran, Mary was chosen by God. Despite the fact that she was poor, still among all women of the world she became the most respected one. Image of Mother Mary as the ideal woman in classical Turkish poetry appears in diferent guises with signiicant emphases on her greatest virtues such as chastity, modesty and sacriice to prayer. Besides, Mary appears as the mother of Jesus. The writers have often emphasized on how miraculously Mary gave birth to Jesus. their ability to create, “give birth to poetry”, is the miracle of the similar sort. The present article deals with the peculiarities of Mother Mary image interpretation by individual poets. Furthermore, the author is trying to deine its place in imagional ield of poetry in general, and also trying to ind out the speciics of the features that poets give to this image. Besides, artistic qualities and importance of metaphors, tropes and stylistic igures used in poetization of Mother Mary have been analyzed.